AB030. Prevalence and incidence of bronchiectasis in Catalonia in 2012 - Monteagudo, Mònica (J Thorac Dis, 2016)
BACKGROUND: Bronchiectasis is a pulmonary disorder defined morphologically as a permanent airway dilatation of different etiologies such as cystic fibrosis, infections or immunodeficiencies. The true incidence and prevalence of non-cystic fibrosis bronchiectasis are not well known. To determine the prevalence and incidence of bronchiectasis (BC) not due to cystic fibrosis in primary care patients in Catalonia (Spain) in 2012. To describe the clinical characteristics and treatment patterns of BQ patients and to estimate the health burden associated with BQ. METHODS: Data was obtained from SIDIAP database (Information System for the Development of Research in Primary Care) from Catalonia. The prevalence was estimated with all the patients with a codified diagnosis of BQ at 31st December 2012. Descriptive statistics were performed to describe the study population. RESULTS: A total of 20,895 patients with BQ were identified by the end of 2012. Of them, 2,703 patients were newly diagnosed in 2012. The prevalence of BQ was 3.6 cases per 1,000 inhabitants, with higher rates among women compared to men (3.9 vs. 3.3). The incidence of BQ was 4.8 cases per 10,000 inhabitants, with higher rates among women than men (4.9 vs. 4.6). Both prevalence and incidence increased with age in both genders and the highest prevalence and incidence was estimated for men aged 65 to 99 years (prevalence, 15.2 cases per 1,000 inhabitants; incidence, 21.9 cases per 10,000 inhabitants). For all the patients diagnosed with BQ, mean age was 68.3 years [standard deviation (SD): 15.6], with an equal distribution among genders (53.9% of women). The mean duration of the disease at the time of the study was 4.4 years [interquartile range (IR): 2.0–7.6]. During the previous year, 11.2% of patients had a spirometry performed, 55.9% of patients had at least one exacerbation, 12.6% were hospitalized and 89.9% had a visit in primary care. Regarding treatment, 7.3% were on antibiotics, 2% were treated with ICS and 1.9 with a LABA. CONCLUSIONS: The prevalence of BQ in Catalonia increases with age, especially in men ≥65 years. There is a high use of health resources in patients with BQ.